МАКЕДОНСКИОТ ЈАЗИК НИЗ ОПШТЕСТВЕНИТЕ ПРОМЕНИ (Philological Studies, 2019)
Macedonian language as the official language in the Republic of Macedonia becomes the language of education, science, the media, and the institutions within the social and political system. In linguistics, sixty-five years are a relatively short period of time for more noticeable changes to take place in the grammar of a language. However, some changes can be seen at every level of a language. The most important factors that influence the changes in a language are the popular dialects and the strong influence of the Serbo-Croatian language in the period from 1945 to 1990, as well as the prestige of the Skopje dialect. From 1990 to today, the globalization process could also be included, which is felt through the strong influence of the English language.